2011
DOI: 10.5506/aphyspolb.42.261
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Our primary task is to demonstrate that the logarithmic nonlinearity in the quantum wave equation can cause the spontaneous symmetry breaking and mass generation phenomena on its own, at least in principle. To achieve this goal, we view the physical vacuum as a kind of the fundamental Bose-Einstein condensate embedded into the fictitious Euclidean space. The relation of such description to that of the physical (relativistic) observer is established via the fluid/gravity correspondence map, the related issues, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
93
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(106 citation statements)
references
References 38 publications
(62 reference statements)
4
93
0
Order By: Relevance
“…Some versions of SVT favor a logarithmic Schrödinger equation [41]. Given the apparent resemblance between the Higgs boson and the dilaton mentioned earlier in the Introduction, the formulation herein could be fruitful in investigating this direction.…”
Section: Discussionmentioning
confidence: 99%
“…Some versions of SVT favor a logarithmic Schrödinger equation [41]. Given the apparent resemblance between the Higgs boson and the dilaton mentioned earlier in the Introduction, the formulation herein could be fruitful in investigating this direction.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the theory allows us to establish the initial conditions for inflation, for primordial perturbations and for spontaneous symmetry breaking [5,6]. That is, the quantum cosmology is a theory of initial conditions.…”
Section: Introductionmentioning
confidence: 99%
“…This has already been shown at the nonrelativistic level in [59], so in the current study we will investigate the relativistic case. The effective low-energy Lagrangian for the Maxwell field interacting with small fluctuations of the physical vacuum was proposed in [54], along with a mass generation mechanism which was analogous to the Higgs one. In this paper we propose a different mass generation mechanism which uses the same Lagrangian, except that the scalar potential is assumed to be "upended".…”
Section: Physical Vacuummentioning
confidence: 99%
“…One of the candidate theories lies within the framework of the superfluid vacuum approach [46][47][48][49][50][51]. This theory is based on the idea [52][53][54] that a physical vacuum can be viewed as some sort of background superfluid condensate described by the logarithmic wave equation (the latter was studied previously on grounds of the dilatation covariance [55] or separability [56][57][58]). It was shown that small fluctuations of the logarithmic condensate obey the Lorentz symmetry and can be interpreted not only as the relativistic particle-like states but also as the gravitational ones [54] depending on a type of mode.…”
Section: Physical Vacuummentioning
confidence: 99%
See 1 more Smart Citation